1982
DOI: 10.1524/zkri.1982.159.14.173
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphie, Leitfähigkeit und Kristallstrukturen von Oxo-phthalocyaninato-titan(IV)

Abstract: Oxo-phthalocyaninato-titan(IV) (PcTiO) shows weak electrical conductivity of 5 · 10~1 0 Ω" 1 cm" 1 at room temperature. Doping of PcTiO with I 2 is accompanied by an increase of conductivity up to 5· 10" 3 Ω" 1 cm" 1 . PcTiO was found to exist in two modifications built up by monomeric complexes: Phase I crystallizes monoclinic in the space group Ρ 2 l /c with the lattice constants a = 1341.1(6) pm, b = 1323.0(3) pm, c = 1381.0(4) pm, β = 103.72(3)°, Ζ = 4. Phase II forms a triclinic structure in space group P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
87
1
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(99 citation statements)
references
References 12 publications
10
87
1
1
Order By: Relevance
“…The calculated Ti-N and Ti-O bond distances (indicated in Fig. 2) compare well with the averaged values of 2.07 and 1.64 Å respectively determined from X-ray crystallography [18].…”
supporting
confidence: 76%
“…The calculated Ti-N and Ti-O bond distances (indicated in Fig. 2) compare well with the averaged values of 2.07 and 1.64 Å respectively determined from X-ray crystallography [18].…”
supporting
confidence: 76%
“…Different dimeric structures are possible, with two PC macrocycle planes parallel and the Al-OH oriented in the same direction (head-to-tail) or in the opposite direction (head-to-head or tail-to-tail). Similar results were observed for trivalent metal Pc's (21,(33)(34)(35)(36). Thus, the X-ray structure determinations of single crystals of several vacuum-deposited thin film Pc's that have a trivalent or tetravalent metal at centre (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…PcGaC1, PcAlCl, PcInC1, PcVO) have shown that they have the tendency to aggregate in the solid state in either a cofacial stack (head-to-tail) or in various interleaved slipped stacks (head-to-head or tail-to-tail). It was proposed that the slipped configuration, in which the two PC phases have more degree of movement than the a -or P-phases reported before for other Pc's (22,23), is responsible for the strongly red-shifted visible absorbance spectra (33)(34)(35)(36). Infrared spectroscopy has been used by a number of authors as an indicator of crystallographic phase for phthalocyanines (23,26,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structures of phase I and phase I1 TiOPc have been determined. [32] These films could be intermediate between amorphous and crystalline phase 11.…”
Section: Advanced Materialsmentioning
confidence: 99%